PENGARUH MANAJEMEN LABA DAN MEDIA EXPOSURE TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) PADA PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - YASIN, MUHAMMAD (Universitas 17 Agustus 1945 Surabaya, 2020)
ABSTRACTThe aim offthis research is to findeempirical evidence about (1) the influence of profitability to CSR disclosure, (2) the influence of leverage to CSR disclosure, (3) the influence of earning management to CSR disclosure, and (4) the influence offmedia exposure to CSR disclosure. The populations of this research are companies manufacturing sector consumption goods industry which is listed on the Indonesian Stock Exchange (IDX) in the period of year 2014-2016. The research samples are 20 companies with 60 observations. In this study, the variables used are profitability measured by Return On Asset (ROA), leverage measured using Total Debt To Total Assets (TDA), earning management measured using Discretionary Accrual (DA), and media exposure measured by dummy variable. The analysis method usediis multiple linear regression analysis with the instrument SPSS (Statistical Product and Service Solution). The result oftthis research indicates that profitability does not have significant positive effect on CSR, leverage does not have significant positive effect on CSR, earning management does not have significant positive effect on CSR, and media exposure has a significant positive effect on CSR. It has been found from the determination coefficient (R2) that the R square value is 0,478 or 47,8%, which means the ability of profitability, leverage, earning management and media exposure in explaining CSR disclosure variable as the dependent variable is still weak because it has R < 0,5.